Description of odontogenic infection cases at the Oral Surgery Polyclinic of Hasan Sadikin Hospital Bandung, Indonesia - Savitri, Ravitha; Karasutisna, Tis; Nurwiadh, Agus (Universitas Padjadjaran, 2012)
One of the most difficult cases to be managed in dentistry is an odontogenic infection. The study was aimed to finding the description of the odontogenic infection cases at the Oral Surgery Polyclinic of Hasan Sadikin Hospital, Bandung, Indonesia, according to the odontogenic infection types, genders, ages, sources of infection, and type of treatment given. This study was a retrospective-descriptive study with a survey method conducted from January 2009 to December 2010. The results of this study showed that there were total 8 types of odontogenic infection cases. The periapical abscess was the most frequent abscess found in 89 patients (30.6%). Male patients were having more often cases than women with the ratio of 53:47. The most frequent age group was the 21-30 years old age group in 57 patients (22.7%). The highest number of patients from 8 different cases of odontogenic infection (30.2%). The source of odontogenic infection was found most commonly by the mandibular first molar teeth, with as much as 26.6%.